Study of the Effect of Thickness and Annealing Process on Optical Properties of (SnO2:5%Cu) Thin Films - Hakim T. Kadhim, et.al (Al-Qadisiyah Journal of Pure Science, 2017)
Thin films of SnO2:5%Cu have been prepared on slide glass using chemical spray pyrolysis technique. The optical constants were studied in accordance to the recording of the absorptance and transmittance spectra in range of wave-lengths (350-900) nm . The following optical constants have been calculated: (absorption coefficient , Reflectance, extinction coefficient,refractive index, dielectric constant in its two parts, and optical conductivity) as afunction of photon energy.